Deregulated expression of the HSP40 family members Auxilin-1 and -2 is indicative of proteostasis imbalance and predicts patient outcome in Ph+ leukemia. Issue 1 (December 2015) - Vieri, Margherita; Geng, Huimin; Patterson, John; Panse, Jens; Wilop, Stefan; Samali, Afshin; Chevet, Eric; Masouleh, Behzad
Abstract Background Proteostasis is defined by the orchestrated control of anabolic and catabolic protein pathways. Disruption of proteostasis results in cell stress and adaptation to proteostasis imbalance is mediated by adaptive pathways such as the Heat Shock Response (including heat-shock proteins) or the unfolded protein response (UPR). The BCR-ABL1 kinase (Philadelphia chromosome) is the hallmark of chronic myeloid leukemia (CML) and defines a historically poor subset in acute lymphoblastic leukemia (Ph+ ALL). We previously demonstrated the importance of the UPR and particularly of the IRE1/XBP1 signaling axis in Ph+ ALL, while others demonstrated the therapeutic relevance of HSP70 in ALL. In this regard, HSP70 is regulated by smaller HSP40 s, whose function is so far poorly characterized. Results Herein, we characterize the expression of HSP40 s in Ph+ ALL and CML. We show that these genes are not regulated in a pan-class manner and identify a homologous gene pair, namely Auxilin-1 (DNAJC6) and Auxilin-2 (GAK) with a unique expression profile. Overexpression of Auxilin-2, the ubiquitously expressed homologue of Auxilin-1 correlated with superior clinical outcome in ALL and was tightly linked to both IRE1 RNase and BCR-ABL1 kinase activities. Conclusions Our findings suggest that HSP40 gens are uniquely regulated and provide a rationale for further studies between BCR-ABL1/IRE1-based therapies in combination with HSP40 inhibitors, thus opening potentially novel therapeutic avenues.